Auxin Does the SAMba: Auxin Signaling in the Shoot Apical Meristem - Pernisová, Markéta; Vernoux, Teva (Cold Spring Harbor perspectives in biology, 2021)
Plants, in contrast to animals, are unique in their capacity to postembryonically develop new organs due to the activity of stem cell populations, located in specialized tissues called meristems. Above ground, the shoot apical meristem generates aerial organs and tissues throughout plant life. It is well established that auxin plays a central role in the functioning of the shoot apical meristem. Auxin distribution in the meristem is not uniform and depends on the interplay between biosynthesis, transport, and degradation. Auxin maxima and minima are created, and result in transcriptional outputs that drive the development of new organs and contribute to meristem maintenance. To uncover and understand complex signaling networks such as the one regulating auxin responses in the shoot apical meristem remains a challenge. Here, we will discuss our current understanding and point to important research directions for the future.
Keywords: kyseliny indoloctové; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; signální transdukce; Meristem; Signal Transduction; meristém; Indoleacetic Acids